A study on torrefaction of Laminaria japonica - Uemura, Y. (Elsevier, 2015)
Torrefaction of a macroalga Laminaria japonica, a representative macroalga, was carried out in a fixed-bed tubular reactor under nitrogen atmosphere at 423 to 573 K. Three useful findings were obtained for torrefaction of L. japonica from this study. Firstly, the major reaction of the microalga may be decomposition of alginate, while the major reaction for torreterrestrial biomass is known to be decomposition of hemicellulose. Even so, H/C vs. O/C (so-called the van Krevelen plot) showed a similar trend between the macroalga and terrestrial biomass. Secondly, an extremely low temperature is effective to obtain a satisfactory energy yield of torrefied macroalga. Thirdly, the ash, nitrogen and sulfur can be considerably eliminated from the macroalga by torrefaction. Â© 2015 Elsevier B.V. All rights reserved.